Orações adjetivas não-prototípicas do português: relações discursivas e gramaticais - Amorim, Monika Benttenmuller (2011)
A study of the relative clauses of the Portuguese language, based on written texts selected from short stories and editorials, belonging to the fifteenth century and the twenty-first century. Constructions consisting of phrasal clauses represented in its non-prototypical type are analyzed. Two types of non-prototypical adjective clauses are observed: those that refer to an antecedent noun phrase represented by the clausal arrangement .That + comments and those that refer to a block of ideas, represented by the clausal arrangement .In which + comments. The functional linguistic theory is the basic theory support to this work, considering the interdependence between semantics and syntax and also from a perspective of studying language from a continuum point of view. The methodological approaches have a bias both qualitative (case study, comparative method, analysis of the status of the references, taken into consideration if the comments were considered positive or negative) and quantitative (tabulation and frequency), with emphasis on the first bias. The semantics independence of these constructions could be verified in its illocutionary force. Based on data collected, it was concluded that the relationship between the non-prototypical adjective clauses is not of a syntactic dependency, but a discursive association (AZEREDO, 1997), which means the confirmation of the hypothesis that they are located near the left edge of the continuum in the chart proposed by Hopper & Traugott, 1993, that is, in a different position from where the prototypical adjective clause is located.